A novel method to measure T1‐relaxation times of macromolecules and quantification of the macromolecular resonances. Issue 2 (30th August 2020) - Murali‐Manohar, Saipavitra; Wright, Andrew Martin; Borbath, Tamas; Avdievich, Nikolai I.; Henning, Anke
Abstract : Purpose: Macromolecular peaks underlying metabolite spectra influence the quantification of metabolites. Therefore, it is important to understand the extent of contribution from macromolecules (MMs) in metabolite quantification. However, to model MMs more accurately in spectral fitting, differences in T1 relaxation times among individual MM peaks must be considered. Characterization of T1 ‐relaxation times for all individual MM peaks using a single inversion recovery technique is difficult due to eventual contributions from metabolites. On the contrary, a double inversion recovery (DIR) technique provided flexibility to acquire MM spectra spanning a range of longitudinal magnetizations with minimal metabolite influence. Thus, a novel method to determine T1 ‐relaxation times of individual MM peaks is reported in this work. Methods: Extensive Bloch simulations were performed to determine inversion time combinations for a DIR technique that yielded adequate MM signal with varying longitudinal magnetizations while minimizing metabolite contributions. MM spectra were acquired using DIR‐metabolite‐cycled semi‐LASER sequence. LCModel concentrations were fitted to the DIR signal equation to calculate T1 ‐relaxation times. Results: T1 ‐relaxation times of MMs range from 204 to 510 ms and 253 to 564 ms in gray‐ and white‐matter rich voxels respectively at 9.4T. Additionally, concentrations of 13 MM peaks are reported. Conclusion: A novel DIR method is reported in this work to calculate T1 ‐relaxation times of MMs in the human brain. T1 ‐relaxation times and relaxation time corrected concentrations of individual MMs are reported in gray‐ and white‐matter rich voxels for the first time at 9.4T. Abstract : Click here for author‐reader discussions